PENGARUH LATIHAN LEG PRESS TERHADAP PENINGKATAN KEKUATAN OTOT TUNGKAI PADA ATLET LEMBAGA KARATE-DO INDONESIA TAMBANG - M. Ilham Seppinriaudy; Ramadi Ramadi; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The purpose of this study was to determine the effect of leg muscle strength training on athletes of the Karate-Do Indonesia Tambang institute. This research was conducted at Dojo Lemkari Tambang Jl.Cipta Karya, Pekanbaru, Riau. This research was conducted from August 2020 to September 2020 by implementing 16 meetings with 3-4 times a week. The population in this study were 10 athletes from the Karate-Do Indonesia Mining Institute. The sample is part of the number and characteristics of the population. Based on the results of the research and data processing carried out, it can be concluded as follows: there is a significant effect of leg press exercise (X) on the leg muscle strength of the Mine Lemkari athletes (Y). Based on the t-test analysis, it produces a t count of 8 and a t table of 1.833. T table is obtained from the degree of freedom or degrees of freedom denoted by (db) with the formula V = n-1, which is 10-1 = 9 (1,833) which is obtained from the t-test table, it can be concluded that Tcount> Ttable and Ha. It can be concluded that there is an effect of leg press training on the increase in leg muscle strength in Lemkari Tambang athletes at the level of 90 0.05 with a 90% confidence level.Key Words: Jump Rope Training, Slowly, Endurance Tennis Team